2020
DOI: 10.1101/2020.04.23.058024
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Directional biases in whole hand motion perception revealed by mid-air tactile stimulation

Abstract: Human machine interfaces are increasingly designed to reduce our reliance on the dominantly used senses of vision and audition. Many emerging technologies are attempting to convey complex spatiotemporal information via tactile percepts shown to be effective in the visual domain, such as shape and motion. Despite the intuitive appeal of touch as a method of feedback, we do not know to what extent the hand can substitute for the retina in this way. Here we ask whether the tactile system can be used to perceive c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…The ability of mid-air haptics to produce complex spatial and temporal tactile stimuli has thus presented neurscientists with uncharted new territories for research and knowledge generation. For example, Perquin et al asked whether the tactile system can be used to perceive complex whole hand motion stimuli, and whether it exhibits the same kind of established perceptual biases as reported in the visual domain [78]. To that end, they designed user studies that confirmed human hand ability to discriminate tactile motion direction, and affirmed the presence of a tactile 'Oblique Effect' (analogous to that observed in vision) where users are both better and more confident at discriminating motion in the vertical and horizontal axes of the hand, compared to those stimuli moving obliquely.…”
Section: Neuroscience Research Studiesmentioning
confidence: 99%
“…The ability of mid-air haptics to produce complex spatial and temporal tactile stimuli has thus presented neurscientists with uncharted new territories for research and knowledge generation. For example, Perquin et al asked whether the tactile system can be used to perceive complex whole hand motion stimuli, and whether it exhibits the same kind of established perceptual biases as reported in the visual domain [78]. To that end, they designed user studies that confirmed human hand ability to discriminate tactile motion direction, and affirmed the presence of a tactile 'Oblique Effect' (analogous to that observed in vision) where users are both better and more confident at discriminating motion in the vertical and horizontal axes of the hand, compared to those stimuli moving obliquely.…”
Section: Neuroscience Research Studiesmentioning
confidence: 99%